2013
DOI: 10.1007/s10827-013-0470-8
|View full text |Cite
|
Sign up to set email alerts
|

A geometric understanding of how fast activating potassium channels promote bursting in pituitary cells

Abstract: The electrical activity of endocrine pituitary cells is mediated by a plethora of ionic currents and establishing the role of a single channel type is difficult. Experimental observations have shown however that fast-activating voltage- and calcium-dependent potassium (BK) current tends to promote bursting in pituitary cells. This burst promoting effect requires fast activation of the BK current, otherwise it is inhibitory to bursting. In this work, we analyze a pituitary cell model in order to answer the ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…For example, variations in the time constant of dendritic delayed-rectifier potassium conductance inactivation induces the transition between the repetitive spiking and bursting states [5]. Variations in the time constant of BK conductance activation induce the transition between the repetitive spiking and bursting states [6]. Similarly to these two cases, the present study demonstrated that variations in the time constant were involved in the transition between the repetitive spiking and bursting states.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…For example, variations in the time constant of dendritic delayed-rectifier potassium conductance inactivation induces the transition between the repetitive spiking and bursting states [5]. Variations in the time constant of BK conductance activation induce the transition between the repetitive spiking and bursting states [6]. Similarly to these two cases, the present study demonstrated that variations in the time constant were involved in the transition between the repetitive spiking and bursting states.…”
Section: Discussionsupporting
confidence: 64%
“…For example, changes in the time constant of dendritic delayed-rectifier potassium conductance inactivation induce a nonlinear effect on the dynamic states of the ghostbursting model [5]. In a mathematical model that has been derived based on pituitary lactotroph cell data, bursting dynamics appears when the time constant of fast-activating voltage-and calcium-dependent potassium (BK) conductance activation is fixed at a smaller value, whereas spiking dynamics appears when the time constant is fixed at a larger value [6]. In addition, it is implied that changes in the time constant of delayed-rectifier potassium conductance activation play an important role in modulating the dynamic states of the Stern model [4].…”
Section: Introductionmentioning
confidence: 99%
“…; Vo et al . ). Pseudo‐plateau bursting has been proposed to increase intracellular Ca 2+ to a greater extent than spiking alone which is thought to be important in driving hormone secretion in endocrine cells (Van Goor et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Vo et al . ) yet display predominantly spontaneous single spike activity but can transition to pseudo‐plateau bursting when stimulated (Kuryshev et al . ; Van Goor et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wechselberger et al reported that a class of three-dimensional canards, called type-I folded nodes, produces small-amplitude oscillations in MMOs [60]. Afterwards, several studies applied canard theory to the CB model of neurons to predict the number of STOs per spike in MMOs [6165]. However, further research has yet to explore how the mathematical results of such studies relate to the neuronal electrophysiological mechanisms.…”
Section: Introductionmentioning
confidence: 99%